Tuyển chọn và nghiên cứu phân loại của các chủng nấm men sinh Coenzyme Q10 phân lập ở Việt Nam - Đào, Thị Lương (Đại học Quốc gia Hà Nội, 2016)
Screening of 80 yeast strains belong to 12 genera containing CoQ10, are storing at Vietnam Type Culture Collection. The content of CoQ10 in 9 strains (11.25%) were high (> 2 mg/g biomass), 33 strains (41,25%) were from 1.0≤CoQ10<2 mg/g biomass and 38 strains (47.5%) had levels <1.0 mg/g biomass. Among the nine yeast strains had high CoQ10 content, 5 strains belonged to the genus Cryptococcus, the remaining four strains of 3 genera, including Rhodosporium, Trichosporon and Dexomyces. Of 9 strains, seven strains were isolated from Phong Nha-Ke Bang National Park. D1/D2 26S rDNA sequence analysis and the morphological characteristics showed that three strains (S02, S09.5 and S13.2) were affiliated to Cryptococcus podzolicus, strain S09.4 belonged to Hannaella sinensis, strain VY140 was Derxomyces haininhensis, and strain DN2.3 was considered to represent a new species.